Acoustic-phonetic performance of vowels in Chilean Spanish speakers with early Parkinson’s disease - Martínez-Cifuentes, Renato; Soto-Barba, Jaime (Revista de Investigación en Logopedia, 2022)
The articulation of consonant and vowel linguistic sounds is impaired in Parkinson’s Disease (PD). In vowels, this alteration manifests, acoustically, in the formantic structure and in the vowel space area. As there has been no research on this subject in Chile, this study aimed at contrasting the acoustic-phonetic performance of vowels in Chilean Spanish speakers with early PD with healthy speakers. A quantitative, quasi-experimental, correlational study was carried out. 15 speakers with PD (M=69.6 years, SD=7.46) and 15 healthy speakers (M=70.07 years, SD=7.75) read 30 phrases containing the five vowels of Chilean Spanish. The center frequencies (F1 and F2) and the bandwidths (B1 and B2) of the vowel formants, and five indexes of the vowel space area were all analyzed. Differences were found in B2 of /i/ and /u/ between speakers with PD and healthy speakers; in F1 of /e/ and /u/, in F2 of /u/, in B1 of /e/ and in B2 of /o/ between male speakers with PD and healthy male speakers; and in B2 of /i/ between women with PD and healthy women (p<.05). As such, the acoustic performance of vowels in Chilean Spanish speakers with Parkinson’s disease is thereby reported.